INTELLECTUAL CAPITAL, FIRM PERFORMANCE AND PRESIDENT DIRECTOR LEVEL OF EDUCATION AND SPECIALIZATION - Sietas, Syarine Geannah; Widianingsih, Luky Patricia; Ismawati, Anastasia Filiana (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This study was conducted to determine the effect of intellectual capital on company performance, with the level of education and specialization of the President Director as moderating variables.Research Method. The sample used in this study is a non-financial state-owned company listed on the Indonesia Stock Exchange for the period 2015-2019. Data collection uses secondary data derived from company annual reports. Data analysis used simple linear regression and moderated regression using SPSS 25.Research Result and Findings. This study indicates that intellectual capital has a positive effect on company performance as proxied by ROA. The President Director’s educational background variables, namely education level, and specialization, cannot moderate the effect of intellectual capital on company performance.